False and genuine decoherence in the early universe: a local observer and time-averaged observables - Fumiya Sano; Junsei Tokuda (Journal of High Energy Physics)
Abstract We study quantum decoherence of curvature perturbations at superhorizon scales caused by the gravitational nonlinearities. We show that cubic gravitational couplings, constrained by the spatial diffeomorphism invariance, lead to infrared (IR) and ultraviolet (UV) divergences in the decoherence rate at one loop. These divergences arise respectively from deep IR fluctuations, which appear as background modes to a local observer, and from violent zero-point fluctuations in the deep UV. We argue that these divergences are unobservable, as they vanish when proper observables are considered. We consider correlators defined using the geodesic distance for IR divergences and time-averaged correlators for UV divergences. To incorporate these observer’s perspective, we propose to use in effective quantum state, defined in terms of actual observables, as a more appropriate probe of the quantum coherence of the system measured by an observer. We then evaluate the finite decoherence rate induced by superhorizon environment during inflation and in the late universe.